Determining effective bending stiffness of fabrics and other materials from tests involving an added weight. Issue 1 (January 2020) - Plaut, Raymond H
It is often desired to determine the bending stiffness of a fabric or other material. Some simple tests have been utilized for this purpose. The tests considered here involve a horizontal cantilever, vertical cantilever, hanging ring, heart loop and hanging pear loop. Usually a strip or loop of material is only subjected to its self-weight in these tests. In some cases, an additional weight is applied and causes greater deformation; this problem is analyzed here. In each test, the position of an extreme point is measured under the self-weight and applied load. Polynomial approximations are proposed to obtain the bending stiffness of the material.